1992
DOI: 10.1083/jcb.119.6.1387
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of axonal growth in the vertebrate nervous system by interactions between glycoproteins belonging to two subgroups of the immunoglobulin superfamily.

Abstract: We acknowledge the critical reading of the manuscript of Drs. Klaus Hermann, Thomas Jentsch, Colin Henehan, and Brian Boycott. We would also like to thank Dagmar Boshold and Ursula Sogo for secretarial assistance, and Dr. Stephan Klauser for helping us with figures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
90
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 97 publications
2
90
0
Order By: Relevance
“…The neural cell adhesion molecule L1 in the mouse [Ng-CAM, 8D9 or G4 as possible homologs in the chicken (Lagenaur and Lemmon 1987;Grumet 1992;Sonderegger and Rathjen 1992)] is an integral cell surface glycoprotein (Rathjen and Schachner 1984;Faissner et al 1985) and was originally defined as an adhesion molecule because antibodies against it inhibited cell adhesion and aggregation . Lemmon et al (1989) showed that antibodies to chicken and mouse L1 block neurite outgrowth from mouse neurons, thus confirming that mouse and chicken L1 interact homophilically.…”
Section: Introductionmentioning
confidence: 99%
“…The neural cell adhesion molecule L1 in the mouse [Ng-CAM, 8D9 or G4 as possible homologs in the chicken (Lagenaur and Lemmon 1987;Grumet 1992;Sonderegger and Rathjen 1992)] is an integral cell surface glycoprotein (Rathjen and Schachner 1984;Faissner et al 1985) and was originally defined as an adhesion molecule because antibodies against it inhibited cell adhesion and aggregation . Lemmon et al (1989) showed that antibodies to chicken and mouse L1 block neurite outgrowth from mouse neurons, thus confirming that mouse and chicken L1 interact homophilically.…”
Section: Introductionmentioning
confidence: 99%
“…L1 also binds heterophili-cally to axonin-1, TAG-I, F3/Fll, and phosphacan (34,71). L1 regulates axon targeting, axon fasciculation, cell migration, and synaptic plasticity (3,36,38,39,51,71). Interactions of L1 with the fibroblast growth factor receptor (13,77) and pp60 ~src (25) appear to play an important role in its morphogenetic actions.…”
mentioning
confidence: 99%
“…Calcium-independent binding of L1 molecules in adjacent membranes (homophilic binding) promotes cell-cell adhesion and activates a tyrosine kinase signaling cascade involved in neurite outgrowth (36,77,79,81). L1 also binds heterophili-cally to axonin-1, TAG-I, F3/Fll, and phosphacan (34,71). L1 regulates axon targeting, axon fasciculation, cell migration, and synaptic plasticity (3,36,38,39,51,71).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Axon-associated cell-adhesion molecules (AxCAMs), concentrated primarily on axons and growth cones, are known to play a prominent role in pathfinding decisions influenced by the local environment. AxCAMs are divided in three major groups; cadherins (Takeichi et al, 1991 ;Ranscht et al, 1994), integrins (Reichardt and Tomaselli, 1991) and neural surface proteins of the immunoglobulin superfamily (Sonderegger and Rathjen, 1992;Brummendorf and Rathjen, 1993). One subgroup of the Ig superfamily consists of Fll(contactin)/F3, TAG-l/axonin-1 and PANGBIG-I (Briimmendorf et al, 1989;Ranscht, 1988;Gennarini et al, 1989;Furley et al, 1990;Zuellig et al, 1992;Connelly et al, 1994;Yoshihara et al, 1994).…”
mentioning
confidence: 99%